Enhanced CO2 Photoreduction through Spontaneous Charge Separation in End‐Capping Assembly of Heterostructured Covalent‐Organic Frameworks. Issue 50 (10th November 2022) - Lin, Huaxing; Liu, Yuan; Wang, Zirui; Ling, Liying; Huang, Hao; Li, Qiaohong; Cheng, Linxiu; Li, Yibao; Zhou, Jilong; Wu, Kaifeng; Zhang, Jian; Zhou, Tianhua
Abstract: It is well known that charge separation is crucial for efficient photocatalytic solar conversion. Although some covalent‐organic frameworks (COFs) exhibit visible‐light harvest, the large exciton binding energies reduce their photocatalytic efficiencies. Herein, we developed a novel method to post‐treat the olefin‐linked COFs with end‐capping polycyclic aromatic hydrocarbons (PAHs) for spontaneous charge separation. Interestingly, a type‐II heterostructure is constructed in our perylene‐modified COFs which displays drastically enhanced performance for photocatalytic CO2 reduction, with an efficiency of 8‐fold higher than that of unmodified COF. A combination of electrochemical, steady‐state, and time‐resolved spectroscopic measurements indicates that such drastically enhanced performance should be attributed to photoinduced spontaneous charge separation in the heterostructure. These results illustrate the feasibility of engineering the charge‐separation properties of crystalline porous frameworks at a molecular level for artificial photosynthesis. Abstract : An efficient end‐capping strategy is developed to construct intramolecular heterostructures by incorporating polycyclic aromatic hydrocarbons (PAHs) into covalent‐organic frameworks (COFs). Thanks to the photoinduced spontaneous charge separation between COFs and PAHs, the heterostructured COFs exhibit outstanding activity and selectivity for photocatalytic reduction of CO2 to CO.